Train-Bridge Dynamic Behaviour of Long-Span Asymmetrical-Stiffness Cable-Stayed Bridge - Yuexing Wu (Hindawi Limited, 2021)
Long-span cable-stayed bridge (LCB) with unequal-height towers is being designed and constructed in metro lines due to its better adaptability to environment and terrain conditions compared to traditional cable-stayed bridge with equal-height towers. However, the asymmetrical arrangement of towers leads to obvious nonuniformity of the structural stiffness along the longitudinal direction, which intensifies the wheel-rail coupled vibration behaviour, and affects the running safety of operating trains and ride comfort. Therefore, train-bridge dynamic behaviour of long-span asymmetrical-stiffness cable-stayed bridge is deeply investigated in this work. Primarily, considering the comprehensive index of frequency difference and modal assurance criterion (MAC), a nonlinear model updating technique (NMUT) based on penalty function theory is proposed, which can be used to optimize the bridge numerical model. Secondly, on the basis of the train-track-bridge dynamic interaction theory (TDIT), a train-track-bridge coupled dynamic model (TCDM) is established. Finally, a LCB with unequal-height towers is applied as a case to illustrate the influence of asymmetrical stiffness on the train-track-bridge dynamic characteristics. Results show that the proposed NMUT is efficacious and practical. For the LCB with unequal-height towers, a significant difference between the bridge vibration at low tower location and that at high tower location appears. The vertical displacement difference of the main beam on both sides of the bridge increases with the distance from the observation point to the bridge tower increasing. The variation of acceleration difference on both sides of the bridge is influenced by the speed of the train and the position of the observation point simultaneously. In general, vibrations of the main beam at low tower location are larger than those at high tower location.